An Anarchist Life : Mollie Steimer (1897-1980) - Avrich, Paul, 1931-2006 (S.l. : s.n., 1980)
From the celebrated Russian intellectuals Michael Bakunin and Peter Kropotkin to the little-known Australian bootmaker and radical speaker J. W. Fleming, this book probes the lives and personalities of representative participants of this anarchist movement. In this volume, Paul Avrich captures the flavor of a time when anarchism was a vital part of a worldwide struggle against political and social injustice. The biographies here have a powerful cumulative effect that makes one fully aware of the influence of the anarchist movement during its heyday in the nineteenth and early nineteenth centuries -- and of the appeal that its ardent champions had for members of protest movements during the 1960s and 1970s. The book focuses chiefly on Russian and American anarchists and their influence on each other, but it includes discussions of Germany, France, Mexico, Brazil, and other countries, and of the numerous international connections within the anarchist movement
Keywords: Steimer, Mollie, -- 1897-1980.